Media campaign study of the Oral Therapy Extension Programme (OTEP II) - UNICEF (© UNICEF, 2016)
1. Introduction 2. Characteristics of respondents 3. Awareness of khabar saline 4. Awareness on mass media messages on khabar saline 5. Awareness on mass media messages on diarrhoea prevention 6. Use patterns of and attitudes towards khabar saline 7. Performance of field workers